Acoustic stimulation of the human round window by laser-induced nonlinear optoacoustics - Liza Lengert; Michael Tomanek; Mohammad Ghoncheh; Hinnerk Lohmann; Nils Prenzler; Stefan Kalies; Sonja Johannsmeier; Tammo Ripken; Alexander Heisterkamp; Hannes Maier (Scientific Reports, 2024)
Abstract The feasibility of low frequency pure tone generation in the inner ear by laser-induced nonlinear optoacoustic effect at the round window was demonstrated in three human cadaveric temporal bones (TB) using an integral pulse density modulation (IPDM). Nanosecond laser pulses with a wavelength in the near-infrared (NIR) region were delivered to the round window niche by an optical fiber with two spherical lenses glued to the end and a viscous gel at the site of the laser focus. Using IPDM, acoustic tones with frequencies between 20 Hz and 1 kHz were generated in the inner ear. The sound pressures in scala tympani and vestibuli were recorded and the intracochlear pressure difference (ICPD) was used to calculate the equivalent sound pressure level (eq. dB SPL) as an equivalent for perceived loudness. The results demonstrate that the optoacoustic effect produced sound pressure levels ranging from 140 eq. dB SPL at low frequencies ≤ 200 Hz to 90 eq. dB SPL at 1 kHz. Therefore, the produced sound pressure level is potentially sufficient for patients requiring acoustic low frequency stimulation. Hence, the presented method offers a potentially viable solution in the future to provide the acoustic stimulus component in combined electro-acoustic stimulation with a cochlear implant.